Les objets intermédiaires de conception comme instruments de l’activité : quels apports dans une démarche de conception inclusive et participative de technologies ambiantes à destination des personnes fragilisées ? - Elena Elias; Marc-Éric Bobillier Chaumon (Activités)
This paper presents a participatory and inclusive design approach to the development of emerging ambient home support technology for vunerable elderly people. With this approach, we wish to both determine real needs and prospect the technological acceptance of a homecare voice assistant - including a machine learning AI engine- based on the activity and experience of these users with specific needs. To this end, users are integrated into the design process as full-fledged actors; the idea is that the device is designed with, by and for the users, despite their difficulties and deficiencies that might prove to be an obstacle to their commitment. For this purpose, we designed intermediate design objects to support and accompany the participatory design approach. They serve as supports during co-design actions to foster collaboration and coordination between actors.